Migrantenquartiere: Ressource oder Benachteiligung? - Andreas Farwick (Räumliche Auswirkungen der internationalen Migration, 2014)
For several decades Germany has registered high rates of immigration. Migrant labourers from Turkey and Southern Europe and their descendants who have long been residents in Germany form the largest group of persons with a migration history. The second largest group consists of ethnic Germans who mainly immigrated into Germany from the successor states of the former Soviet Union and from other East European states in the 1990s after the breakdown of communist regimes. The majority of those with migration backgrounds live in large cities and - because of their relatively low incomes - are concentrated particularly in less attractive working class neighbourhoods or in residential areas with a high percentage of social housing. The paper examines the reasons for and social consequences of the spatial concentration of migrant population in the urban migrant quarters. These quarters facilitate newly arrived migrants in adapting to the new environment by providing social networks. Migrants gain social and mental stability. But increasing length of the stay in these quarters has a distinctly negative effect on the migrants' integration process especially as a consequence of their spatial concentration in residential areas characterised by low income groups. – – Seit mehreren Jahrzehnten ist ein hohes Maß an Zuwanderung nach Deutschland zu verzeichnen. Die größten in Deutschland lebenden Migrantengruppen bilden die seit längerem ansässigen Arbeitsmigrant(inn)en aus Südeuropa und der Türkei sowie die deutschstämmigen (Spät)Aussiedler(innen) aus den ehemaligen Ostblock-Staaten, die vor allem in den 1990er Jahren nach dem Zusammenbruch der kommunistischen Regierungen zugewandert sind. Räumlich konzentrieren sich die Migrant(inn)en und ihre Nachkommen vorwiegend in den größeren Städten und hier aufgrund ihres vergleichsweise geringen Einkommens in den weniger attraktiven Arbeiterquartieren und den Siedlungen des sozialen Wohnungsbaus. Der Beitrag fragt nach den Ursachen und sozialen Folgen der räumlichen Konzentration der Zuwanderinnen und Zuwanderer in den Migrantenquartieren der Städte. Deutlich wird, dass diese Quartiere über die positiven Effekte der sozialen und psychischen Stabilisierung in der Anfangsphase der Eingliederung im Aufnahmeland hinaus insbesondere aufgrund der mit der räumlichen Konzentration von Migrant(inn)en einhergehenden sozioökonomischen Segregation einkommensarmer Bevölkerungsgruppen deutlich negative Effekte auf den Eingliederungsprozess von Migrant(inn)en haben.
urn:nbn:de:0156-0754123; hdl:10419/106651; http://econpapers.repec.org/RePEc:zbw:arlfob:3
Keywords: 710; Zuwanderung; Migrantenquartiere; Restriktionen; Präferenzen; soziales Kapital; soziales Lernen; Diskriminierung; Binnenintegration; institutionelle Vollständigkeit; Soziale Stadt; Immigration; migrant quarters; constraints; preferences; social capital; social learning; discrimination; societal integration by interior integration; institutional completeness; programme "Social City“